Cayley-type theorems for g-dimonoids - Yolchyan, Marlen; Movsisyan, Yuri (Armenian Journal of Mathematics, 2022)
In this paper we prove Cayley-type theorems for g-dimonoids using the left (right) acts of sets and concept of dialgebra.